The The right to food and a new international approach: Food sovereignty (Legal journal - Research in Legal and Social Sciences, 2017)
There is a latent reality that has afflicted us for several decades: Hunger and poverty, both are constantly growing worldwide; especially affecting rural populations where the majority of people are dedicated to activities related to agriculture. Alarming figures warn us about this silent crisis "hunger", daily, in the world 100,000 people die of hunger or due to immediate consequences; There are approximately 826 million people who suffer from chronic malnutrition. These people suffer, according to the FAO, from "extreme hunger", consume 300 calories a day and survive in subhuman conditions. Among the most affected are Sub-Saharan Africa, Haiti, Afghanistan, Bangladesh, North Korea and Mongolia. We are faced with a never-ending vicious circle, a hereditary curse, where every day a malnourished mother gives birth to a malnourished child who suffers from the same problem. Governments, multilateral organizations, non-profit organizations and different foundations have tried to mitigate its consequences, over the years, through different programs and policies implemented.
Keywords: food security; malnutrition; food sovereignty; Right to food